The Effect of Product Differentiation and Service Quality Satisfaction on Consumer Satisfaction - Isnawati, Isnawati; Adiansyah, Adi; Dahlena, Alni; Hamdani, Nizar Alam; Maulani, Galih Abdul Fatah; Solihat, Asri; Soni, Mohammad (Jurnal Inovasi Bisnis dan Kewirausahaan, 2024)
The importance of understanding the complex dynamics between product differentiation, service quality, and consumer satisfaction in the ever-evolving digital era. Service quality is associated with purchasing decisions, where consumers are more likely to be satisfied if the company provides services that meet or exceed consumer expectations. The purpose of this study is to identify and analyze consumer satisfaction from product differentiation and the quality of services that have been provided. The research method used is a quantitative descriptive study by analyzing the influence of consumer satisfaction, data collection techniques using observation and questionnaires, data analysis is carried out by testing validity, reliability and multiple linear regression. The results of data analysis show that the coefficients are interpreted that the constant value with a significance of 0.598 and the value of the dependent variable, namely Y, is 0.00. The coefficients in the variable coefficient model, in particular, help reveal the dynamics of the relationship when the influence of the independent variable on the dependent variable varies depending on time or other conditions. Therefore, Service satisfaction from product diversity also provides an optimal impact on people's lives.